La logica delle emozioni: una teoria che precorre le scoperte neuroscientifiche - Turri, Maria Grazia (Rivista Italiana di Filosofia del Linguaggio, 2015)
Piecing together the scattered fragments of Peirce’s sign theory it is possible to form what to be a comprehensive emotion theory, coherent with an actual neuroscience theory of emotion, because in his emotion theory the emotion’s role is relevant to memory, apprehension, cognition and evaluation. An emotion is a legisign because every emotion has certain law-like features, it has a pattern unrolling over a period of time, it exists only through instances and is a system of explanation, because exists through instances or replicas, as tokens to a type. Peirce held that the immediate object of a sign, or the object under a specific description, is relative to circumstances of time and place and it is easily identifiable in expressions of emotion. The dynamic object of an emotion as sign could only be known, by the ideal completion of an investigation revealing the class of all things giving rise to a particular emotion and the emotion products a dynamic affect. Interpretants are immediate and dynamic, and can be emotional, energetic, or logical, but the first for importance is the emotional interpretant. Peirce’s contributions to emotion, sentiment, perception, sensation, habit, consciousness, cognition, and community were both highly original and heavily influenced by the main intellectual currents of his time.